G-Protein Subunit Gαi in Mitochondria, MrGPA1, Affects Conidiation, Stress Resistance, and Virulence of Entomopathogenic Fungus Metarhizium robertsii - Youmin Tong (Frontiers in Microbiology, 2020)
G proteins are critical modulators or transducers in various transmembrane signaling systems. They play key roles in numerous biological processes in fungi, including vegetative growth, development of infection-related structures, asexual conidiation, and virulence. However, functions of G proteins in entomopathogenic fungi remain unclear. Here, we characterized the roles of MrGPA1, a G-protein subunit Gαi, in conidiation, stress resistance, and virulence in Metarhizium robertsii. MrGPA1 was localized in the mitochondria. MrGpa1 deletion resulted in a significant reduction (47%) in the conidiation capacity, and reduced expression of several key conidiation-related genes, including fluG, flbD, brlA, wetA, phiA, and stuA. Further, MrGpa1 disruption resulted in decreased fungal sensitivity to UV irradiation and thermal stress, as determined based on conidial germination of ΔMrGpa1 and wild-type (WT) strains. Chemical stress analysis indicated that MrGpa1 contributes to fungal antioxidant capacity and cell wall integrity, but is not involved in tolerance to antifungal drug and osmotic stress. Importantly, insect bioassays involving (topical inoculation and injection) of Galleria mellonella larvae revealed decreased virulence of ΔMrGpa1 strain after cuticle infection. This was accompanied by decreased rates of appressorium formation and reduced expression of several cuticle penetration-related genes. Further assays showed that MrGpa1 regulated intracellular cyclic AMP (cAMP) levels, but feeding with cAMP could not recover the appressorium formation rate of ΔMrGpa1. These observations suggest that MrGpa1 contributes to the regulation of conidiation, UV irradiation, thermal stress response, antioxidant capacity, and cell wall integrity in M. robertsii. This gene is also involved in insect cuticle penetration during infection. These findings raise the possibility of designing powerful strategies for genetic improvement of M. robertsii conidiation capacity and virulence for killing pests.